Microstrip antenna design using different aperture coupling structure - Zhi Wei, Low (Penerbit UTM, 2007)
The wireless industry has experienced a significant growth in the past several years. There is an essential need for a light weight with a low profile and a good performance antenna for wireless application. In order to meet these demands, printed circuit patch antenna is one of the solutions to it. There are four feedings techniques for microstrip antennas which can be categorized as contacting feed and non-contacting feed. For contacting feed, there are microstrip feed and coaxial feed while non-contacting feed are proximity feed and aperture coupled feed. However, for microstrip feed and coaxial feed, the antennas are characterized by bandwidth limitation, which is about 1-2%. To overcome this problem, aperture coupled microstrip antenna (ACMA) was introduced by researchers for the purpose to improve the antenna performance features, especially its bandwidth. Their features have met the essential needs for wireless application which requires a light weight characteristics with a low profile and a good performance antenna. The structure consists of two substrates, one containing the radiating patch and other containing the feed network. A small aperture located under the patch allows coupling of the patch to the feed line which has the form of an open-circuited stub. The input impedance can be controlled by its size, position, and shape of the aperture and open-ended stub length. In this paper, the aperture coupled microstrip antenna with different aperture shape is investigated in terms of its return loss, bandwidth and radiation pattern. Every shape gives a different performance.